On genre-format approaches in the process of defining the phenomenon of "multimedia journalism" - Safaryan, Arman (Bulletin of Yerevan University B: Philology, 2022)
The article examines the terms“Internet journalism” (digital journalism), “convergent journalism” and “multimediajournalism”, often used as “synonymous terms” to denote new forms of journalisticactivity, in connection with the use of the Internet by journalists as a platform for disseminating information. The traditional genres of journalism are being “revised” toreveal their potential “coverage” of multimedia phenomena. It is proposed to define theconcept of “multimedia journalism” through the prism of genre-format approaches, asdespite the existing methodological differences in the scientific literature regardinggenre-forming and format-forming features, the mutually transitive nature of the processes of multimedization and the new genre-format solutions have become obvious.